Réponses

2013-05-13T10:11:55+02:00

n°70:

1) pour x=0.5

E=4*0.5²+8*0.5-5

E=1+4-5

E=0

 

2a) F= (2x+2)²-9

     F= 4x²+8x+4-9

     F=4x²*8x-5

 

2b) F=(2x+2)²-9

       F=(2x+2)²-3²

       F=(2x+2-3)(2x+2+3)

       F=(2x-1)(2x+5)

 

2c) d'après le 2a, on a F=E donc E=(2x-1)(2x+5)

2013-05-13T10:40:48+02:00

1)

 

E= 4x² +8x -5 

 

si x=0.5 

 

E= 4x 0.5² + 8x 0.5 -5

E= 4x 0.25 + 4 - 5 

E= 1 + 4 - 5 

E=0 

 

2) 

a)

F= (2x+2)² -9 

F= (2x+2) (2x + 2) -9 

F= 4x² + 4x + 4x 4 - 9 

F= 4x² + 8x  -5 

 

b) 

 

F= 4x² + 8x - 5 = 4(x² + 2x) -5

 

c) 

 

E= 4x² + 8x - 5 = 4(x² + 2x ) -5 

E=F

 

ex 61 

 

x² -6x +9 = (x-3)²  identité remarquable  de la forme (a-b)²

x² - 16 = (x-4) (x+4)  IR  de la forme a²-b²

25 + x² -20x = non

2x² + 12x + 3² = non

9x² - 25 = non

49a² + 42a - 9 = non

x² - 81 =  (x-9) (x+9)  IR de la forme a² - b²

1 - 100x² = non

4x² + y² = non